(untitled) (Eurasian Research Bulletin, 2023)
In our country, the production of spare parts for cars and equipment from metal and non-metal materials, which is developing year by year, is developing in a combined manner. In this article, it is explained how important the production of metal powder products, which are successfully used in the national economy, is important for the machine-building and automobile industry, and that extensive work is being carried out on new models and methods of technological processes.